2014
DOI: 10.1016/j.bpj.2014.07.049
|View full text |Cite|
|
Sign up to set email alerts
|

Ligand-Induced Protein Responses and Mechanical Signal Propagation Described by Linear Response Theories

Abstract: In this study, a general linear response theory (LRT) is formulated to describe time-dependent and -independent protein conformational changes upon CO binding with myoglobin. Using the theory, we are able to monitor protein relaxation in two stages. The slower relaxation is found to occur from 4.4 to 81.2 picoseconds and the time constants characterized for a couple of aromatic residues agree with those observed by UV Resonance Raman (UVRR) spectrometry and time resolved x-ray crystallography. The faster "earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(73 citation statements)
references
References 46 publications
(103 reference statements)
3
70
0
Order By: Relevance
“…This form of the LRT is useful for predicting structural changes teins upon ligand binding. 24 Tamura and Hayashi used molecular dynamics data with LRT to determine global conformational changes upon ligand binding. 25 Hirata developed an LRT to study the structural dynamics of perturbed proteins.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This form of the LRT is useful for predicting structural changes teins upon ligand binding. 24 Tamura and Hayashi used molecular dynamics data with LRT to determine global conformational changes upon ligand binding. 25 Hirata developed an LRT to study the structural dynamics of perturbed proteins.…”
Section: Methodsmentioning
confidence: 99%
“…steric interaction regions: (i) between the helix and the tail (residues 23-35 and 74-77) and (ii) the helix and the N-terminal beta strand (residues 1-11 and[23][24][25][26][27][28][29][30][31][32][33][34][35]. Although allosteric interactions between these regions are not yet identified, there are hints from NMR spectroscopy that points to possible interaction36 : residues Lys11, Lys29, and Lys33, each of which is in one of the proposed allosteric interaction regions show order parameter peaks.…”
mentioning
confidence: 99%
“…59 Yang et al formulated a general linear response theory to address the physical nature of protein conformational changes. 60 Inspired by our UVRR study, they applied the theory to calculations of the Mb protein response to CO dissociation. Their calculations demonstrated that the theory agreed well with the primary protein changes revealed by our measurements.…”
Section: ¹1mentioning
confidence: 99%
“…Their calculations demonstrated that the theory agreed well with the primary protein changes revealed by our measurements. 60 …”
Section: ¹1mentioning
confidence: 99%
See 1 more Smart Citation